Performance of Myco-coagulant from Lentinus squarrosulus for turbidity reduction in a settling column - Mamun, Abdullah Al; Jebun, Nessa; Alam, Md Zahangir; Ahmad Raus, Raha; Nedjai, Radhia (2022)
The sedimentation process in river water by a myco-flocculant was investigated using a settling column. Kaolin suspension was used as synthetic turbid water. Particle size analysis was conducted using a laser particle size analyser. Settling column test was conducted to determine the detention time and overflow rate of the particles which can be used to design sedimentation basin for water treatment plants. The detention time and overflow rate of kaolin suspension and river water were 59.5 minutes and 41.6 m/day for 80% turbidity removal and 63 mins and 29.25 m/day for 65% turbidity removal, respectively. The new myco-flocculant has potential for reducing river water turbidity that is non-toxic as well as biodegradable, and therefore may be encouraging to water treatment plant in future applications. However, further studies are required to assess the storage, stability and economic feasibility of myco-coagulant for reducing turbidity from raw river water.